Modeling an agroclimatic zoning methodology to determine the potential growing areas for Cyamopsis tetragonoloba (Guar gum) in Argentina - Falasca, Silvia Liliana (2015)
In the last few years, world demand for guar gum (Cyamopsis tetragonoloba L) has grown considerably and its price has increased consequently. Guar bean is a grain legume with potential as a summer crop in Argentina under subhumid, semiarid and arid climate. In Argentina, the cultivation of guar has not been established, and this research was conducted to explore this possibility. The authors developed an agro-climatic zoning methodology for guar bean in Argentina, based on the bioclimatic requirements of the crop. Using as reference the climatic data from regions where cluster bean is grown in the world, the authors analyzed the average climate data provided by the National Meteorology Service to identify the potential area suited to cluster bean production in Argentina. This model may be applied in any part of the world, using the agroclimatic limits presented in this work. To obtain the maps, a series of previously interpolated bioclimatic variables were used. Afterwards, these were processed with the Geographic Information System tool of the Arc-GIS 9.3 program. The agroclimatic zoning was obtained by superimposing the following three maps: frost-free days, annual rainfall and average temperature during growing period. As a result, ten classes of agroclimatic suitability were classified: optimal, very suitable, very suitable with complementary irrigation, suitable with complementary irrigation, suitable under humid and subhumid regime, suitable with constrains under tropical and temperate climate, marginal and non suitable. The suitable areas are distributed from the North of Argentina to 40ºLatitude.